Dressler’s like pericarditis with pericardial effusion is the presenting feature of infective endocarditis - Majumder, Biswajit; Chatterjee, Sharmistha; Sarkar, Rakesh; Chatterjee, Pritam Kumar (Nepalese Heart Journal, 2018)
Summary: Infective Endocarditis (IE) being primarily the disease of valves and endocardium may occasionally be complicated with pericardial involvement in the form of pericarditis and pericardial effusion (PE). Pericarditis may be observed incidentally at the time of diagnosing IE and rarely does it remain the presenting feature of IE .The pericardial effusion may be attributed to ruptured aortic abscess extending into the pericardial space, autoimmune reaction, renal failure, HIV and congestive heart failure (CHF). Here we are presenting a 42 year old male having IE with vegetation in both mitral and aortic valve along with large sterile pericardial effusion was treated successfully by the medical therapy alone with favorable outcome. IE presenting with large exudative pericardial effusion being treated without any surgical intervention with substantial resolution of effusion has not been reported so far in medical literature.Nepalese Heart Journal 2017;12(2): 43-44.